Dribbling Practice Method Using Instep Drive Technique Against Dribbling Speed In Soccer - Biqi Fajar Sidiq; Dicky Reva Apriana Sanga Dwi (STKIP Muhammadiyah Kuningan, 2024)
This study was conducted to determine the effect of the dribble training method using tht instep drive technique on the speed of dribbling in football which was carried out in class V SD Negeri 2 Caracas. This research is a quantitative research, with sampling technique using cluster random sampling technique. In this sampling technique, a class draw will be conducted at SD Negeri 2 Caracas which consists of 6 classes, by choosing randomly and the results of the selection in class V as an experimental class totaling 32 students and for data collection this research uses a test instrument. Based on the results of this study, it shows that the speed of dribbling from dribbling exercises using instep drive in the experimental class where the pretest has the fastest time of 14.09 and the longest time of 19.54 with an average result of 17.07 pretest and posttest has the fastest time of 10.54 and the longest time of 17.23 with an average posttest result of 14.07 so that the average increase in pretest and posttest is 3.00. In addition, in the experimental class, hypothesis testing was also carried out using the t-test which obtained a significance result of 0.000 0.005, meaning that there was a difference between the results of the pretest and posttest scores so that the dribble training method using the turtle foot technique had an effect on the speed of dribbling in football.